Hybrid data synchronization mechanism for mobile computing - Xiao-long XU; Xiao-xiao LIU (Tongxin xuebao)
The hybrid data synchronization mechanism (HDSM) was proposed,which integrates centralized architecture and ad hoc architecture together,and a series of self-organization domains (SOD) were built as to cut down the traffic of synchronization data and lighten the load of synchronization server.The capacity-value-based data distribution strategy was proposed,which establishes data distribution paths of SOD tree based on the comprehensive processing capacity of mobile nodes to implement the high-efficient data transmission.The increment capture strategy based on track changes was proposed,which captures operation logs with triggers and obtains pure increment data by purification.The experi-mental results show that HDSM can make maintenance of data consistency better in mobile computing environment and shorten the response time of synchronization,and reduce the traffic of data synchronization and the load of synchroniza-tion server.